Phalloplasty: The dream and the reality - Mamoon Rashid; Muhammad Sarmad Tamimy (Indian Journal of Plastic Surgery)
Phalloplasty has come a long way as Plastic Surgery has evolved over the years. The complication ridden multistage tube pedicles popularized by Gillis were, with the advent of microsurgery, replaced by radial forearm flaps. The composite osteo-cutaneous version of this flap promised ′All for one and one for all′ assuring both a reliable urinary conduit and a phallus stiffener. Prelamination and prefabrication to make the neo-urethra came with the promise of reducing both fistula and strictures but that did not happen and flap failure rates increased. Penile stiffeners of various types have been introduced; the artificial ones were associated with high infection and failure rates and are best inserted after the neo-penis regains some sensitivity. With the introduction of perforator flaps the Anterolateral thigh flap in its sensate pedicled form has started replacing the Radial forearm free flap as the first choice flap because of a hidden donor area and lack of microsurgical expertise requirement. Being sensate it tolerates a stiffener better. It is now possible to reconstruct an aesthetically pleasing glans as well, thus meeting both the aesthetic and functional desires of the patient. Complications encountered in this reconstructive effort include flap failure, urethral fistula, urethral stricture and stiffener related problems.